Analisis Kebijakan Anggaran Rumah Detensi Imigrasi Berdasarkan Peraturan Menteri Hukum Dan Hak Asasi Manusia Ri No.M.05.Il.02.01 Tahun 2006 Tentang Rumah Detensi Imigrasi (Studi Kasus Rudenim Medan) - Geovany Manurung; H. Abdul Razak Nasution; Hasdiana Juwita Bintang (Journal of Mandalika Literature, 2025)
Based on the Regulation of the Minister of Law and Human Rights of the Republic of Indonesia No. M.05.IL.02.01 Year 2006, the budget policy analysis of Medan Immigration Detention Center (Rudenim) is discussed in this research. It is very important to protect human rights because of the existence of the Rudenim as a temporary shelter for foreign nationals (WNA) who violate immigration provisions. The empirical juridical method is used in this research, which collects data through interviews and observations at the research location. According to the results of the research, the budget allocated for the provision of food and beverages in Medan Detention Center has not fully met the needs and preferences of detainees from various cultural backgrounds. This has an impact on the health and well-being of detainees, who are often uncomfortable with the food served. In addition, this research shows how the IDC creates new services to improve detainees' experience and implements budget policies that are in line with standards. It is hoped that this research will provide recommendations for the improvement of the Rudenim's budget policies and services for the welfare of detainees as the “My Hobby Is” innovation provides a space for detainees to express themselves and reduce stress by doing cooking and gardening activities.